Multiple facets of HIV-associated renal disease - da Silva,D.R. (2016)
HIV infection has a broad spectrum of renal manifestations. This study examined the clinical and histological manifestations of HIV-associated renal disease, and predictors of renal outcomes. Sixty-one (64% male, mean age 45 years) HIV patients were retrospectively evaluated. Clinical presentation and renal histopathology were assessed, as well as CD4 T-cell count and viral load. The predictive value of histological lesion, baseline CD4 cell count and viral load for end-stage renal disease (ESRD) or death were determined using the Cox regression model. The outcomes of chronic kidney disease (CKD) and ESRD or death were evaluated by baseline CD4 cell count. The percent distribution at initial clinical presentation was non-nephrotic proteinuria (54%), acute kidney injury (28%), nephrotic syndrome (23%), and chronic kidney disease (22%). Focal segmental glomerulosclerosis (28%), mainly the collapsing form (HIVAN), acute interstitial nephritis (AIN) (26%), and immune complex-mediated glomerulonephritis (ICGN) (25%) were the predominant renal histology. Baseline CD4 cell count ≥200 cells/mm3 was a protective factor against CKD (hazard ratio=0.997; 95%CI=0.994-0.999; P=0.012). At last follow-up, 64% of patients with baseline CD4 ≥200 cells/mm3 had eGFR >60 mL·min-1·(1.73 m2)-1 compared to the other 35% of patients who presented with CD4 <200 cells/mm3 (log rank=9.043, P=0.003). In conclusion, the main histological lesion of HIV-associated renal disease was HIVAN, followed by AIN and ICGN. These findings reinforce the need to biopsy HIV patients with kidney impairment and/or proteinuria. Baseline CD4 cell count ≥200 cells/mm3 was associated with better renal function after 2 years of follow-up.